ANALISIS EFEKTIVITAS KERJA PEGAWAI BAGIAN ADMINISTRASI FISIP UNDIP - Maesaroh, Maesaroh (JURNAL ILMU SOSIAL, 2013)
Administration   Section  Fisip   Undip  was  one  part   of conducting both administrative and academic, so itwas expected to assist the implementation of Tri Dhanna of Higher Education to effectively and efficiently.   The  problems   were   believed   to  often   occur   in  the administration Fisip Undip include the uneven work load, duplication / twinningfonn,  the existence of role ambiguity The things that allegedly led to less optimal effectiveness of employee activity was Good work was less clear, so often overlapping, supervision was less intense and less than optimal and less communication were good, especially the external / with stakholder, then the problem was fonnulated  "not optimal effectiveness of existing employees at the Administration Fisip Diponegoro  University, Semarang" . The purpose  of the studed  to determine the effectiveness of employee  activity,  work  procedures,  supervision  and  administration section Fisip Undip communications and test the hypothesis among the variables. The theory used was the theory about the effectiveness of the Steers that the effectiveness of employee activity was the attitude or the general condition of someone who was positive about organizational life and  there were 4 factors  that also contribute  to the final  success of an organization  including: organizational  characteristics,  environmental characteristics,   worker   characteristics,   policies   and   management practices.   The  results  showed   that:  The  effectiveness  of  employees working in the administration Fisip Undip could say was good.